Comparative Analysis of Crypto Systems Using Biometric Key - Muftuoglu, Zumrut; Yildirim, Tulay (ELSEVIER SCIENCE BV, 2019)
In digital world, the security of data is one of the most important issues. Biometric cryptosystems provide great convenience and security by combining biometrics and cryptography. The aim of this paper is to provide a good standpoint into the state-of-the-art and current research directions of crypto systems using biometric key, including theory and applications. (C) 2019 The Authors. Published by Elsevier Ltd.
Keywords: Biometrics; Key Generation; Cryptography; Computer Science; Telecommunications